Semi-Markov models for the evaluation of time, location, magnitude and depth of earthquakes in southern Peru 2023 - Risco Franco, Carlos (2024)
Peru is located in the South Pacific seismic region and frequently experiences significant earthquakes. Among the most relevant events are the 8.4 magnitude earthquake in Arequipa in 2001, the 7.9 magnitude earthquake in Ica in August 2007 and again a 6.3 magnitude earthquake in Arequipa in July 2017. These events underscore the need for seismic risk studies in the region. This study is of a descriptive and correlational type, with a cross-sectional design, whose objective is to identify the areas in southern Peru with the highest risk of experiencing high magnitude earthquakes. The data come from the Geophysical Institute of Peru and cover the period from 1960 to 2023, analyzing earthquakes with a magnitude equal to or greater than 5.5 MW. The methodology of (Sadeghian, 2012), based on the semi-Markov model, was applied to predict time and location of seismic events, extending this model also to depth states. The Pisco-Ica and Chala-Atico areas are highlighted as the most at risk for the occurrence of large magnitude earthquakes.